Dilemma in Timing of Delivery in a Patient with an Acute Myocardial Infarction - Laura M. Héman; Ingrid E. C. Devies; Frans J. M. E. Roumen (Hindawi Limited, 2015)
Introduction. Acute myocardial infarction (AMI) in a pregnant woman is rare. When occurring, AMI is a major cause of maternal and neonatal death. By presenting the following case we describe the dilemma concerning the timing of delivery. Case. A 36-year-old, multiparous women, at 35 6/7 weeks of gestation, suffered from an AMI due to an acute blockage of the left anterior descending artery (LAD). This was treated by angiographic thrombosuction and biodegradable stent placement. Within 5 hours after this procedure, a cesarean section (CS) was performed because of a nonreassuring fetal condition. A healthy son with an Apgar score of 9/10 was born. The patient's postoperative course was complicated by a big wound hematoma, a hemoglobin drop, and heart failure. Discussion. In case of AMI during pregnancy, the cardiological management has absolute priority. The obstetrical management is not outlined. In a nonreassuring fetal condition, delivery is indicated after stabilization of the mother. However, delivery after recent AMI and angiography will bring new risks of cardiologic stress and bleeding complications. The limited literature available tends to an expectant obstetrical management, but this case emphasizes the difficulty of waiting in suspected fetal distress.